Microwave Absorbing Properties of Ba0.6Sr0.4Fe12-zMnzO19 (z = 0 â 3) Materials in XBand Frequencies - Gunanto, Yohanes Edi; Jobiliong, Eric; Adi, Wisnu Ari (Journal of Mathematical and Fundamental Sciences, 2016)
Ba0.6Sr0.4Fe12-zMnzO19 (z = 0,1,2, and 3) were successfully synthesized by solid state reaction through a mechanical milling method. Stoichiometric quantities of analytical-grade MnCO3, BaCO3, Fe2O3, and SrCO3 precursors with purity greater than 99% were mixed. It was found that the best phase composition, having an absorber with high performance, was Ba0.6Sr0.4Fe11MnO19. Refinement of the X-ray diffraction patterns revealed that the Ba0.6Sr0.4Fe11MnO19 was single-phase and had a hexagonal structure (P63/mmc). Mechanical milling of Ba0.6Sr0.4Fe11MnO19 powders produced particles with a mean size of ~850 nm. SEM images revealed the morphology of the particles as being aggregates of fine grains. The magnetic properties of the Ba0.6Sr0.4Fe11MnO19 particles showed a low coercivity and a high remanent magnetization. The Ba0.6Sr0.4Fe11MnO19 has certain microwave absorber properties in the frequency range of 8-14 GHz, with an absorbing peak value of "‘8 dB and -10 dB at frequencies of 8.5 and 12.5 GHz, respectively. The study concludes that the Ba0.6Sr0.4Fe12-zMnzO19 that was successfully synthesized is a good candidate for use as an electromagnetic absorber material.